Pengaruh Gaya Kepemimpinan Transaksional dan Motivasi Kerja Terhadap Kinerja Guru di Sma Negeri 6 Palembang - Putri, Melia Sari Onika; Alie, Juhaini; Roswaty (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze and determine the effect of Transactional Leadership style and work motivation on teacher performance at SMA Negeri 6 Palembang. The Transactional Leadership style emphasizes reciprocal relationships between leaders and subordinates through a system of rewards and supervision, while work motivation serves as the primary driving force influencing teacher productivity. A quantitative approach was used in this study, with primary data collected through questionnaires and interviews. The sample consisted of 75 teachers at SMA Negeri 6 Palembang. Data analysis was conducted using SPSS V27 software, which included validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing. Based on the t-test results, both transactional leadership style and work motivation have a positive and significant effect on teacher performance, with a significance value of 0.001 < 0.05. Furthermore, based on the F-test results, both transactional leadership style and work motivation simultaneously have a significant effect on teacher performance at SMA Negeri 6 Palembang, with a significance value of 0.00 < 0.05.